Optimization of CC-Coil Design for Wireless Power Transfer System with Series-Series Magnetic Resonance Compensation Technique - Mohd Taib , Muhammad Muhaimin; Ponniran, Asmarashid (Journal of Electronic Voltage and Application, 2021)
This study aims to increase the coupling coefficient of the coils and power transfer efficiency (PTE) of the wireless power transfer (WPT) system. WPT system has a severe issue with the PTE as the transfer distance between the transmitter and receiver increases. Therefore, the transmitter and receiver of the single-circular coil (CC-coil) need to be optimized in geometry and shielding to maintain high coupling at an optimum distance. Implementing the series-series (S-S) magnetic resonance compensation technique can increase the PTE of the WPT system. Therefore, the CC-coil is optimized using Ansys Electronics Desktop and co-simulated with the power electronics and compensation circuit using Ansys Twin Builder. The results show that the CC-coils' coupling coefficient increased by 21.38%, with the maximum optimum transfer distance of 34.99 mm. Implementing the S-S magnetic resonance compensation technique can improve the PTE and output power of the WPT system. The power transmitted also varied with the transfer distance which caused by the variation of the input impedance of the system. Hence, it is essential to consider the coil design and compensation circuit to achieve high PTE and output power at a higher transfer distance.